Hepatoprotective Activity of Momordica diocia Roxb Fruits in CCl4 -Induced Hepatotoxicity in Rats: Hepatoprotective activity of Momordica diocia Roxb fruits - P. Shankar, B.R. Prasanna kumar; Mohammed khallel (Iranian Journal of Pharmaceutical Sciences, 2011)
Fruits, leaves and tuberous roots of Momordicia diocia are used in India as a folk remedy for treatment of a wide range of disorders. The objective of this study was to evaluate the hepatprotective activity of the fruits of Momordicia diocia by preparing different extracts and the resultant extract were screened for the hepatprotective activity. The ethyl acetate and ethanolic extracts of Momordicia diocia fruits were prepared and subjected for phytochemical screening and tested for their hepatprotective activity in CCl4-induced hepatotoxicity in rats. Phytochemical screening showed positive test for steroids, triterpenoids and glycosides (Etoh extract). The ethyl acetate and ethanolic extracts showed a significant hepatprotective activity at a dose of 200 mg/kg (p.o.). The results suggested that Momordica diocia fruits possess potential hepatprotective activity against CCl4 hepatotoxicity possibly by antioxidant activity.